Structural and magnetic analysis of electro-magnetic suspension spring. Issue 1 (April 2020) - Saxena, V; Pali, H S
Abstract: Suspension is the term given to the arrangement of springs, shock absorbers and linkages that interfaces a vehicle to its wheels. Unlike conventional suspension systems that smother the vibrations by scattering the vibration energy into waste heat, the regenerative suspension with vitality reaping shock absorbers can change over the generally squandered vitality into electricity. Thus in this work, designing of the suspension spring for Hero Splendor Plus bike by applying Nimonic 80A material. Specifically, it focuses on a static and dynamic study of the suspension spring. This framework uses electromagnets as inactive dampers, which is utilized to lessen displacement and acceleration of spring mass so as to enhance drive ease.